0757 Feasibility of Split Night Sleep Studies in a Pediatric Population at a Tertiary-care Pediatric Sleep Center. (27th April 2018) - McCarty, T; Bourne, B; Wong, M; Travis, J K; Merritt, M P; Brown, M F; Krishna, J
Abstract: Introduction: Standard management of sleep-related breathing disorders (SRBDs) in children requiring PAP includes the completion of a diagnostic polysomnography followed by full-night PAP titration (FNPT). However, the commonly used 2-step process in the pediatric context is costly, resource intensive, and may delay treatment initiation due to long wait times. While split-night PAP titration (SNPT) is frequently sufficient for treatment initiation in adult SRBD, there is currently limited data on the utility of SNPT in pediatric SRBD. This study examines the feasibility of SNPT in a tertiary-care pediatric hospital-based sleep laboratory and presents preliminary data from this project which ultimately seeks to identify patient characteristics associated with successful SNPTs in pediatric populations. Methods: Demographic and pertinent sleep study data were gathered via retrospective sequential chart review for all completed FNPT and SNPT studies conducted between November of 2015 and November of 2017 as part of routine care. In-lab parent and patient education and mask fitting was performed prior to each titration. Using AASM guidelines, titration was classified "optimal", "good", or "adequate" by a board certified sleep physician, and deemed unsuccessful if classified "unacceptable". A one-tailed t -test and two-tailed Fisher's Exact test were used to assess group differences. Results: Data from 166 PAP titration studies, including 132 FNPTs (55.8% male) and 34 SNPTs (70.6% male) were evaluated. Patient ages ranged from 1 to 21 years for FNPTs (mean 12.6 years) and 2 months to 20 years for SNPTs (mean 13.3 years). The average study time on pressures was not statistically significantly different ( t (37) = 9.31, p = 1.54), with 472.6 minutes for FNPTs and 311.0 minutes for SNPTs. In the current sample, 124 (93.9%) of FNPTs and 29 (85.3%) of SNPTs were successful, revealing a non-significant relationship between type of PAP titration study and study outcome ( p = 0.14). Conclusion: We conclude SNPT is feasible and may be used in a subset of pediatric patients. Further examination of our data will be conducted to determine patient characteristics predictive of PAP study outcome. Support (If Any): None.